For a special teenager : a collection of poems from Blue Mountain Arts - Blue Mountain Arts; Schutz, Susan Polis (Boulder, Colo : Blue Mountain Press, 1999)
"Honoring the great potential within every teenager, this collection bridges the communication gap between parents and teenagers with understanding, support, and love."
Keywords: Parent and child -- Poetry; Teenagers -- Poetry; American poetry -- 20th century; Young adult poetry, American; Poetry -- Poetry